91Is rainfall associated with paediatric acute gastroenteritis in an affluent setting? A 21-Year Retrospective Investigation. (2nd September 2021) - Chong, Ka Chun; Chan, Emily; Lee, TC; Kwok, KL; Lau, SYF; Wang, P; Lam, HCY; Goggins, W; Mohammad, K; Leung, SY; Chan, PKS
Abstract: Background: Although many literatures demonstrated heavy rainfall was associated with an increased risk of acute gastroenteritis via contaminated food and water, we hypothesized there is no association between rainfall and paediatric acute gastroenteritis in a setting with high-standard food and water hygiene. Methods: Intestinal infection-related hospital admissions data during 1998-2018 for children under 5 years of age in Hong Kong were collected. Meteorological data were collected from the Hong Kong Observatory. A distributed lag nonlinear model was employed to examine the associations between meteorological factors and the risk of hospital admissions due to acute gastroenteritis. Results: Rainfall did not exhibit a statistically significant association with the risk of paediatric admission due to acute gastroenteritis but low temperature, low and high relative humidity did. The risk was 6.3% higher (95% confidence interval: 0.3% to 12.6%) when temperature was at 15.1 o C (i.e. the 5th percentile). The adjusted relative risk was statistically significantly higher when relative humidity was ≤73.0% or ≥ 84.0%. Conclusions: Text: We suggest rainfall playing a minor role in disease transmission via contaminated food and water in affluent societies like Hong Kong. Instead, we speculate low temperature and humidity extremes have greater impact on transmission through increased stability and infectivity of enteric viruses. Key messages: Weather plays a minor role in food and water contamination in affluent societies. Low temperature and humidity extremes might improve survival of enteric viruses.